Unveiling Humility as an Influential Virtue - Sharma, Lok Raj (International Research Journal of MMC, 2024)
Humility is the quality or condition of having a modest opinion and a candid acknowledgement of one's own and others' strengths and weaknesses. A rudimentary objective of this article is to unveil humility as an influential virtue in various aspects of human interaction and societal dynamics through overviewing secondary qualitative data garnered from books, journal articles and web documents published between 1967 and 2021. Although historical perceptions hold humility as a passive or subservient trait, it emerges as a robust force capable of fostering meaningful connections, enhancing leadership effectiveness, and promoting overall well-being. The research employs a thematic analysis under a qualitative research design, drawing on insights from psychology, philosophy, and religions to unravel the subtle impact of humility on our day-to-day lives. The research findings indicate humility as a virtue that contributes to the establishment of trust, collaboration, and positive social dynamics, thereby influencing the overall structure of communities and organizations. This article is significant as it makes readers recognize the strength of humility that contributes not only to personal development but also to the cultivation of healthier, more collaborative, and more resilient societies.